Pendampingan Peningkatkan Daya Saing UMKM Melalui Digitalisasi dan Perizinan di Kelurahan Uwung Jaya - Susiati, Asriani; Trisavinaningdiah, Amelia; Sari , Riski Ulan (Annusfy : Journal of Multidisciplinary Research, 2025)
This activity aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) through a digital approach and understanding of business licensing. Based on initial observations, MSMEs in Uwung Jaya Village face various obstacles, such as limited knowledge of digital marketing, business management, and financial management, as well as a lack of understanding of the importance of business legality. The activity implemented a combined approach of field observation and educational seminars. The results of the activity showed an increase in MSMEs' understanding of the importance of digitalization and business licensing. Participants demonstrated high enthusiasm and were active in the question-and-answer session. The long-term impact of this activity is increased family economic independence, the creation of new jobs, and the development of local potential with market value